Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (World Bank, Washington, DC, 2016)
The Palestinian economy is not growing enough to raise living standards and reduce high unemployment. The economy has witnessed a sharp deceleration in economic growth, from over 8 percent during 2007-11 to 3 percent during 2012-15. The sharp decline in growth has stifled the economy's ability to create jobs for a growing youth population. Successful reform efforts and strong economic growth helped bring the relative size of the Palestinian overall fiscal deficit down from 24.6 percent of GDP in 2008 to 13 percent in 2010. However, despite these efforts at fiscal consolidation, the deficit to GDP ratio has remained stuck in the 10 - 13 percent range since 2010 -- on the back of a large wage bill and weak revenue performance. The economy has long suffered from the restrictions1 and political instability that continue to constrain private sector activity. In addition, the decline in donor funding from 32 percent of GDP in 2008 to 6 percent in 2015 has significantly contributed to the recent economic weakening. The internal divide between the West Bank and Gaza, which has created a dual regulatory framework, has also negatively impacted economic activity and the tax base.